216k views
9 votes

\sqrt{(p)/(2)-2 } = √(p-8)

User Milan Saha
by
5.4k points

2 Answers

4 votes
2=2^
Explained above
User Firzen
by
5.6k points
5 votes


\boldsymbol{\sqrt{(p)/(2)-2}=√(p-8)}

Cancel the square root on both sides.


  • \boldsymbol{\sf{(p)/(-2)-2=√(p-8) }}

Multiply both sides by 2.


  • \boldsymbol{\sf{p-4=2p-16 }}

Subtract p from both sides.


  • \boldsymbol{\sf{-4=2p-16-p }}

Simplify


  • \boldsymbol{\sf{-4=p-16 }}

Add 16 to both sides.


  • \boldsymbol{\sf{-4+16=p }}

Simplify


  • \boldsymbol{\sf{12=p}}

Swap sides.


  • \boldsymbol{\sf{p=12 \ \ \to \ \ \ Answer}}

Verification


\boldsymbol{\sqrt{(p)/(2)-2}=√(p-8) \ \ \to \ \ \ Exercise \ normal.}

Let p=12.


  • \boldsymbol{\sqrt{(12)/(2)-2}=√(12-8)}

Simplify 12/6 to 6.


  • \boldsymbol{√(6-4)=√(12-8) }

Simplify 6-2 to 4.


  • \boldsymbol{√(4)=√(12-8) }

Since 2×2=4, the square root of 4 is 2.


  • \boldsymbol{2=√(12-8) }

Simplify 12-8 to 4.


  • \boldsymbol{2=√(4) }

Since 2×2=4, the square root of 4 is 2.


  • \boldsymbol{2=2}

Checked ✅


\huge \red{\boxed{\green{\boxed{\boldsymbol{\sf{\purple{Pisces04}}}}}}}

User Yuklia
by
4.8k points